2019
DOI: 10.1111/joa.13054
|View full text |Cite
|
Sign up to set email alerts
|

Vagal baro‐ and chemoreceptors in middle internal carotid artery and carotid body in rat

Abstract: The glossopharyngeal nerve, via the carotid sinus nerve (CSN), presents baroreceptors from the internal carotid artery (ICA) and chemoreceptors from the carotid body. Although neurons in the nodose ganglion were labelled after injecting tracer into the carotid body, the vagal pathway to these baro‐ and chemoreceptors has not been identified. Neither has the glossopharyngeal intracranial afferent/sensory pathway that connects to the brainstem been defined. We investigated both of these issues in male Sprague–Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In order to further characterize peripheral Emx1-Cre expression, we analyzed the Emx1-tdtomato signal in the neural tissue at the carotid bifurcation where the vagus nerve innervates vascular sensory structures such as the carotid body, carotid sinus, as well as the SCG ( F.B. Wang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to further characterize peripheral Emx1-Cre expression, we analyzed the Emx1-tdtomato signal in the neural tissue at the carotid bifurcation where the vagus nerve innervates vascular sensory structures such as the carotid body, carotid sinus, as well as the SCG ( F.B. Wang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to further characterize peripheral Emx1-Cre expression, we analyzed the Emx1-tdtomato signal in the neural tissue at the carotid bifurcation where the vagus nerve innervates the vascular sensory structures such as the carotid body, carotid sinus, as well as the superior cervical ganglion (SCG) (Wang et al, 2019). In the extracted whole-mount preparation ( Figure 4A ), blur Emx1-tdtomato fluorescence was identified at the carotid artery bifurcation and diffusely in the SCG ( Figure 4B&C ).…”
Section: Resultsmentioning
confidence: 99%
“…They also reported that the neurons in the vagus nerve represented between 1%–2% of all vagal sensory neurons. More recent histological studies identified a population of sparse pseudo‐unipolar cells that resembled vagal afferent neurons in cross‐sections of the porcine vagus nerve (Pelot et al, 2020 ; Settell et al, 2020 ) and rat whole vagal trunk (Wang et al, 2019 ). Whereas Plenat and colleagues (Plenat et al, 1988 ) described these neurons as “displaced sensory neurons ” , in this study, we have identified vagal afferent neurons with soma outside the NG and JG as extraganglionic neurons .…”
Section: Introductionmentioning
confidence: 99%